Larsen syndrome in two generations of an Italian family. Issue 6 (December 1976) - Ventruto, V; Festa, F; Sebastio, L; Sebastio, G
Abstract : This paper describes a familial case of Larsen syndrome. Typical anomalies were present in the propositus and 2 of his 6 daughters. In addition, all patients had progressive deafness and the 2 daughters had cleft palate. The certain exclusion of any consanguinity between the couple, suggests, in this instance, the dominant mode of transmission of the syndrome.